IKAN GABUS MEMBANTU PERCEPATAN PENYEMBUHAN LUKA SEKSIO SESAREA (Politeknik Kesehatan Kemenkes Bandung, 2022)
ABSTRACT The postpartum period is the process after the birth of the placenta until the return of the female reproductive organs before pregnancy. In Indonesia, the incidence of births by caesarean section in 2019 was 28.9%. This incidence has the potential to cause infection in caesarean section wounds. Efforts to heal wounds have several factors including nutrition, mobilization, vitamins, and wound care. One of the nutrients that can help wound healing is protein, namely snakehead fish which has albumin protein which is useful for the wound healing process. The purpose of making this Evidence Based Case Report is to find out that snakehead fish can help heal wounds during the puerperium with a history of post caesarean section. The Evidence Based Case Report method used is by searching for evidence through E Data Based from pubmed, Cochrane and google schoolar. This research used the full text inclusion criteria, Randomized Control Trial (RCT) research design, English and Indonesian language, and based on another researches in 2011-2021. According to the purpose of the Evidence Based Case Report, we used three journals in this research, The results of this research can be a solution for the wound healing process in caesarean section. The albumin content produced by amino acids in snakehead fish can improve the wound healing process for caesarean section. The consumption of snakehead fish per day is 100 grams per day.